BEHAVIOUR OF MARINE MICROFLORA TOWARDS ANTIBIOTICS I. SENSITIVITY TOWARDS CHLORTETRA CYCLINE (CTC) - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2025)
The sensitivity of 61 cultures of bacteria isolated from !fish towards chlortetracycline (CTC) at 5 ppm and 20 ppm levels lhas been determined on two solid media, viz; sea water agar (SW A) and a distilled water based medium consisting of peptone, beef extract, glucose and NaCI (PBGA). The cultures employed consisted of (i) gram-negative rods of marine origin viz; Achromobacler, Pseudomonas, Vibrio and Flavobacterium and (ii) gram positive orgaÂ· nisms viz; Micrococci and Corynebacterium. Depending on the inhibition zone diameter, the order of CTC sensitivity was found to be Pseudomonas < Vibrio < Achromoba.cter as determined on PBGA at CTC levels of 5 and 20 ppm. The SWA enhanced the development of resistance in majority of the cultures as compared to PBGA. PBG broth containing CTC at less than 10 ppm exerted a bacteriostatic effect only while that containing 10 ppm or more exerted a bactericidal effect on Achromobacter, Pseudomonas and Micrococci cuhures. The significance of these results in fish preservation by CTC is discussed.